The Sources of Meaning and Meaning in Life Questionnaire in the Norwegian Context: Relations to Mental Health, Quality of Life, and Self-Efficacy. Issue 1 (2nd January 2019) - Sørensen, Torgeir; la Cour, Peter; Danbolt, Lars Johan; Stifoss-Hanssen, Hans; Lien, Lars; DeMarinis, Valerie; Pedersen, Heidi Frølund; Schnell, Tatjana
ABSTRACT: The Sources of Meaning and Meaning in Life Questionnaire (SoMe) offers dimensional measures of meaningfulness, crisis of meaning, and 26 sources of meaning. It allows for a clearer understanding of the variety of existential orientations, which are known to be linked to both mental and physical health. The Norwegian version of the SoMe was validated by testing 925 randomly selected individuals who were representative for the Norwegian population. Reliability scores were satisfactory; factor analyses suggested a 6-factor structure of the sources of meaning scales. Expected patterns of associations with mental health and quality-of-life factors attested the instrument's construct validity: Meaningfulness showed positive relationships to all quality-of-life factors. There was no relationship with anxiety but negative relationships with depression and distress. Crisis of meaning established a strong positive relationship with anxiety, depression, and distress and a negative relationship with quality-of-life factors. Criterion validity was documented by expected differences in meaningfulness and crisis of meaning between groups with and without presence of depression disorder. Self-efficacy correlated strongly with sources of meaning from the dimension "accomplishment" and moderately negatively with sources of meaning from the dimension "vertical selftranscendence."